Odpowiedzi

  • Użytkownik Zadane
2010-04-12T17:19:19+02:00
A) (x+3)(x-7)=x²-7x+3x-21=x²-4x+21

b)-3(2x-1)(x+6)=-3(2x²+12x-x-6)=-3(2x²+11x-6)=-6x²-33x+18

c)-(y-1)(2y+4)=-(2y²+4y-2y-4)=-(2y²+2y-4)=-2y²-2y+4

d)2a²-(a+6)(2a-1)=2a²-2a²+a-12a+6=-11a+6

3)3(x²-1)-(x-3)(x+2) =3x²-3-x²-2x+3x+6=2x²+x+3
  • Użytkownik Zadane
2010-04-12T17:20:43+02:00
A) (x-3)(x-7) = xkwadrat-7x-3x+21=xkwadrat-10x+21
b)-3(2x-1)(x+6) = (-6x+3)(x+6) = -6xkwadrat-36x+3x+18 = 6xkwadrat-33x+18
c)-(y-1)(2y+4) = (-y+1)(2y+4) = -2ykwadrat-4y+2y+4 = -2ykwadrat -2y+4
d)2a(do kwadratu)-(a+6)(2a-1) = (-2akwadrat-12a)(2a-1) = -4a(do 3)+2akwadrat-24a (do 2)+12a = -4 (do 3) -22a (do 2) +12a